Construction of Trans-4-hydroxy-L-proline-producing Escherichia coli and Optimization of Fermentation Conditions - Xinchao Yang; Xinyu Li; Yuanxiu Wang; Yuehui Liu; Fang Wang; Naxin Sun; Chunjiang Ye (Fermentation)
In this study, we combined the citric acid cycle with the biosynthesis pathways of L-proline and L-hydroxyproline to construct a strain that produces L-hydroxyproline directly from glucose and other raw materials, without the addition of L-proline and α-ketoglutarate. The results showed that the level of L-hydroxyproline production was 550 mg/L. Through the optimization of one-way and orthogonal experiments, the optimal shake flask fermentation conditions were obtained, at which time the production of L-hydroxyproline reached 1800 mg/L, which was 3.3-fold higher. The glutamate permease gene GltS was added to the recombinant plasmid pRSFDuet1-p4h-proBA, and the recombinant plasmid obtained was transformed into E. coli T7E by Gibson seamless cloning to obtain the recombinant strain T7E/pRSFDuet1-p4h-GltS-proBA. Finally, by the addition of 30 mmol/L of sodium glutamate, the recombinant strain achieved a yield of L-hydroxyproline of 2150 mg/L, which was about 1.2-fold higher than the yield of L-hydroxyproline without the addition of sodium glutamate.